We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
173
1
avatar

Define $g$ by $g(x)=5x-4$. If $g(x)=f^{-1}(x)-3$ and $f^{-1}(x)$ is the inverse of the function $f(x)=ax+b$, find $5a+5b$.

 Jul 20, 2018
 #1
avatar+21978 
+1

Define $g$ by $g(x)=5x-4$. If $g(x)=f^{-1}(x)-3$ and $f^{-1}(x)$ is the inverse of the function $f(x)=ax+b$,

find $5a+5b$.

 

\(\begin{array}{|rcl|rcl|} \hline g(x)&=& 5x-4 & f(x) &=& ax + b \quad & | \quad x \leftrightarrow y \\ g(x)&=& f^{-1}(x)-3 & x &=& ay + b \\ && & ay &=& x-b \\ f^{-1}(x)-3 &=& 5x -4 & y &=& \dfrac{x-b}{a} \\ f^{-1}(x) &=& 5x -4+3 & f^{-1}(x) &=& \dfrac{x-b}{a} \\ \hline f^{-1}(x) &=& {\color{red}5}x {\color{green}-1} & f^{-1}(x) &=& {\color{red}\dfrac1a} x {\color{green}-\dfrac ba} \\ \hline \end{array} \)

 

compare:

\(\begin{array}{|rcll|} \hline 5 &=& \dfrac1a \\\\ \mathbf{a} &\mathbf{=} & \mathbf{\dfrac15} \\ \hline \end{array} \begin{array}{|rcll|} \hline -1 &=& -\dfrac ba \\\\ 1 &=& \dfrac ba \\\\ b &=& a \\ \mathbf{b} &\mathbf{=} & \mathbf{\dfrac15} \\ \hline \end{array} \)

 

\(\begin{array}{|rcll|} \hline 5a+5b &=& 5\cdot \dfrac15 + 5\cdot \dfrac15 \\ &=& 1+1 \\ &=& 2 \\ \hline \end{array} \)

 

laugh

 Jul 20, 2018

9 Online Users

avatar
avatar
avatar